Remote Sensing of Snow and Its Applications - Nadir Arslan, Ali; Akyurek, Zuhal (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The reprint book of the "Remote Sensing of Snow and Its Applications" Special Issue provides recent studies on all aspects of remote sensing of snow, from retrieving the data to the application. These studies mainly address the following: (a) New opportunities (Copernicus Sentinels) and emerging remote sensing methods, (b) use of snow data in modeling, and (c) characterization of snowpack.